Chiari malformations: not every disability is visible - Prajjwal, Priyadarshi; Farhan, Muhammad; Inban, Pugazhendi; Mitra, Spandana (International Journal of Contemporary Pediatrics, 2022)
In Chiari malformation (CM), portions of the brain or spinal cord is pushed down through the foramen magnum, which is located at the bottom of your skull. This causes a portion of the brain to be in contact with the part of the spinal column-usually the spinal cord. The cerebrospinal fluid, however, may be pushed up through the hole making it difficult to detect in this condition. These are a collection of malformations affecting the cerebellum, pons, and medulla oblongata in the posterior fossa and hindbrain. Problems caused by these malformations range from the lack of the cerebellum to the cerebellar tonsils protruding through the foramen magnum, with or without additional intracranial or extracranial anomalies such as hydrocephalus, encephalocele, syrinx, or spinal dysraphism. CMs can be of several types and are more common in females than in males and in children than in adults. This is because they are growing and developing at a rapid rate, which leads them to have a greater amount of skull growth. In this review article, we discuss the various types of CMs, their pathophysiology, clinical features, imaging characteristics, treatment, and why they form an important complex of rare disorders necessary to be diagnosed early.